Stochastic Regularization and Eigenvalue Concentration Bounds for Singular Ensembles of Random Operators. (27th November 2013) - Chulaevsky, Victor
Abstract : We propose a simple approach allowing reducing the eigenvalue concentration analysis of a class of random operator ensembles with singular probability distribution to the analysis of an auxiliary ensemble with bounded probability density. Our results apply to the Wegner- and Minami-type estimates for single- and multiparticle operators.